Prototype of a new tip developed to be coupled to dental light-curing units for optimizing bonding of orthodontic brackets and accessories - Sergio Luiz Mota Júnior; Márcio José da Silva Campos; Marco Abdo Gravina; Marcelo Reis Fraga; Robert Willer Farinazzo Vitral (Dental Press Editora, 2013)
OBJECTIVE: development of a new device to be coupled to light-curing units for bonding orthodontic brackets and accessories, and test its efficacy in an in vitro mechanical trial. The inner surface of the device is mirrored and is based on physical concepts of light refraction and reflection. The main advantage of such device is the reduced clinical time needed for bonding and the low possibility of contamination during the process. METHODS: One hundred and twenty specimens were used for testing the shear bond strength of brackets bonded with the device. The Adhesive Remnant Index (ARI) was also determined. The sample was divided into 2 groups. In group 1 a halogen light-curing unit was used while in group 2 a led light-curing unit was used. Each group was then subdivided. In subgroups H1 and L1, a conventional light guide rod was used while in subgroups H2 and L2 bonding was performed with the mirrored device coupled to the tip of the guide light rod. RESULTS: The values obtained for the shear bond strength and the ARI in the subgroups were compared. Results showed that there was no statistically significant difference for the shear strength (p > 0.05) and the ARI (p > 0.05) between the subgroups. CONCLUSION: The tests of mechanical trials and the ARI analysis showed that the new device fulfilled the requirements for bonding orthodontic accessories, and that the time for bonding was reduced to half, being necessary only one light exposure.